The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/alr.22313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cranial base repair techniques utilizing a novel cadaveric CPAP model

Abstract: Background: Although recent guidelines for obstructive sleep apnea recommend early postoperative use of continuous positive airway pressure (CPAP) a er endonasal skull base surgery, the time of initiation of CPAP is unclear. In this study we used a novel, previously validated cadaveric model to analyze the pressures delivered to the cranial base and evaluate the effectiveness of various repair techniques to withstand positive pressure. Methods:Skull base defects were surgically created in 3 fresh human cadaver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…Our group has previously taken initial steps to determine the safety of CPAP use post‐ETS for pituitary adenoma. In a 2019 study, Chitguppi et al used pressure sensors in cadaveric head models and found that NSF reconstruction was able to withstand CPAP pressure of 20 cmH 2 O 11 . Future studies in healthy volunteers and eventually patients undergoing ETS for pituitary adenoma may determine the feasibility of restarting CPAP early in these patients with an aim to mitigate the risk of PLS.…”
Section: Discussionsupporting
confidence: 77%
“…Our group has previously taken initial steps to determine the safety of CPAP use post‐ETS for pituitary adenoma. In a 2019 study, Chitguppi et al used pressure sensors in cadaveric head models and found that NSF reconstruction was able to withstand CPAP pressure of 20 cmH 2 O 11 . Future studies in healthy volunteers and eventually patients undergoing ETS for pituitary adenoma may determine the feasibility of restarting CPAP early in these patients with an aim to mitigate the risk of PLS.…”
Section: Discussionsupporting
confidence: 77%
“…Chitguppi et al used the same cadaveric model and showed that the reconstruction of a sellar defect with a nasoseptal flap was able to withstand breach at all delivered CPAPs. 22 Furthermore, the weakest repair with an onlay of oxidized cellulose was able to withstand up to 12 cmH 2 O of pressure. The mean CPAP required for most people is 9.7 AE 2.6 cmH 2 O, which suggests that CPAP may be safe in selected patients based on the reconstructive algorithm used.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with known OSA, multi-layer skull base reconstruction with a nasoseptal flap may provide more robust resistance to postoperative CPAP and prevent postoperative complications. 12,21 Furthermore, 76% of respondents agreed that when OSA is suspected, a preoperative polysomnogram should be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…10 Positive airway pressure may present risks to postoperative patients with skull base defects and most recent research has focused on postoperative management of OSA in patients undergoing endoscopic skull base surgeryfrom timing of CPAP initiation to modification of skull base reconstruction. 7,[11][12][13][14][15] Preoperative screening of surgical patients for OSA has been identified as a way to anticipate and mitigate potential postoperative risks posed by OSA. 6,16,17 However, little is currently known about practice patterns by endoscopic skull base surgeons to screen for OSA in this patient population.…”
Section: Introductionmentioning
confidence: 99%